2020
DOI: 10.1002/aur.2457
|View full text |Cite
|
Sign up to set email alerts
|

Competing Perceptual Salience in a Visual Word Recognition Task Differentially Affects Children With and Without Autism Spectrum Disorder

Abstract: Differences in visual attention have long been recognized as a central characteristic of autism spectrum disorder (ASD). Regardless of social content, children with ASD show a strong preference for perceptual salience—how interesting (i.e., striking) certain stimuli are, based on their visual properties (e.g., color, geometric patterning). However, we do not know the extent to which attentional allocation preferences for perceptual salience persist when they compete with top‐down, linguistic information. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 98 publications
0
9
0
1
Order By: Relevance
“…The enhanced FC between the two suggests that most of the knowledge obtained by preschool boys with ASD from external visual information is limited to atypical visual attention, which is difficult to separate and transfer due to dysfunction of the reward loop. A previous study found that children with ASD prefer to focus on significant visual objects (such as color and geometric patterns) than NC children (spend more time looking at social stimuli), and the more severe the symptoms, the worse the learning ability of children with ASD ( Venker et al, 2021 ). Another study also found that children with ASD who spend more time watching geometric images will show more serious ASD symptoms, a lower intelligence quotient, and lower adaptive skills ( Bacon et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The enhanced FC between the two suggests that most of the knowledge obtained by preschool boys with ASD from external visual information is limited to atypical visual attention, which is difficult to separate and transfer due to dysfunction of the reward loop. A previous study found that children with ASD prefer to focus on significant visual objects (such as color and geometric patterns) than NC children (spend more time looking at social stimuli), and the more severe the symptoms, the worse the learning ability of children with ASD ( Venker et al, 2021 ). Another study also found that children with ASD who spend more time watching geometric images will show more serious ASD symptoms, a lower intelligence quotient, and lower adaptive skills ( Bacon et al, 2020 ).…”
Section: Discussionmentioning
confidence: 98%
“…Repetitive and rigid behaviors and social language development disorders are undoubtedly the most obvious clinical symptoms in ASD, and the strengthening of visual ability also seems to be important in the early stage of ASD. For example, an experiment demonstrated that if a toddler spent ≥69% looking at geometric scenes, the positive predictive effectiveness of accurately classifying children with ASD was 100% ( Venker et al, 2021 ). Moreover, the enhanced visual ability of children at high-risk of ASD at 9 months was related to their severity of ASD symptoms at 15 and 24 months ( Varcin and Jeste, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the salient visual features of electronic toys, such as flashing lights, may compete with other relevant aspects of the child's visual environment (Radesky and Christakis, 2016). Visual salience exerts a strong influence on attention allocation in children with ASD (Sacrey et al, 2014;Venker et al, 2018Venker et al, , 2020. Salient auditory and visual features of electronic toys may decrease the likelihood that children with ASD will engage in joint attention and may cause them to miss important linguistic and social cues (Miller et al, 2017;Healey et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…In natural environments, individuals are often exposed to many stimuli simultaneously. Attention capture by aversive stimuli in these busy natural environments might be a path towards subjective hypersensitivity and experiences of sensory distress and overload; indeed, prior research suggests there may be an elevated propensity towards attentional capture in autism (e.g., (63)(64)(65)). Participants (or parent proxy reporters) completing sensory questionnaires would presumably then report on these experiences of attention capture and sensory distress.…”
Section: Questionnaires and Behavioural Thresholdsmentioning
confidence: 99%